U.S. Filipino Adults Have Elevated Prevalence of Hypertension Across the Adult Lifespan: Findings From a Cross-Sectional Electronic Health Record Study - Nancy P. Gordon, ScD; Irvin C. Lien, MD; Jamal S. Rana, MD, PhD; Joan C. Lo, MD (Elsevier, 2024)
Introduction: The prevalence of hypertension increases with age and differs by race and ethnicity. Among U.S. Asian adults, prevalence is higher for Filipino adults than for other major Asian subgroups, but whether this disparity exists across the adult lifespan is unknown. This study examined hypertension prevalence by age decade, comparing Filipino adults with South Asian, Chinese, Black, Hispanic, and White adults. Methods: This cross-sectional study used 2015-2016 electronic health record data from a Northern California integrated healthcare delivery system for 1,839,603 adults aged 30-79 years, including 128,124 Filipino adults. Hypertension was defined by diagnosis codes. Sex-specific prevalence was calculated by race and ethnicity overall and by 10-year age decade from ages 30-39 years to 70-79 years. The prevalence of hypertension among 5 racial and ethnic groups was compared within each decade (with Filipino as the reference), adjusting for age, English language, diabetes, smoking, and weight category. Results: Decade-specific prevalence of hypertension among Filipino men and women, respectively, was 9.7% and 8.5% for ages 30-39 years, 26.0% and 23.9% for ages 40-49 years, 45.9% and 44.4% for ages 50-59 years, 65.4% and 63.9% for ages 60-69 years, and 82.1% and 82.9% for ages 70-79 years. Across all age decades, hypertension prevalence among Filipino adults largely tracked with Black adults and was much higher than among South Asian, Chinese, White, and Hispanic adults. This pattern remained after adjusting for covariates, with the largest differences observed for adults aged <60 years. Conclusions: Similar to Black adults, Filipino adults have persistently higher hypertension prevalence than South Asian, Chinese, Hispanic, and White adults across the adult lifespan. These findings underscore the importance of surveillance and prevention efforts for this high-risk Asian group beginning in early adulthood.